A Dynamic Utility Maximization Model for Product Category Consumption - Rutger van Oest; Philip Hans Franses; Richard Paap (Tinbergen Institute, 2002)
It is conceivable that the whether to buy and how much tobuy decisions in the purchasing process of households areinfluenced by the inventory process. In this paper we thereforeput forward a model for consumption, where we rely on establishedeconomic theory. We incorporate this model in a model forpurchase behavior. Our consumption specification, which isderived from utility maximization principles, is more flexiblethan an ad hoc approach, which has recently been proposed inthe literature. We illustrate our model for yogurt purchases,and show that our model yields important additional and usefulinsights. One such insight is that promotion anticipationbehavior turns out not only to occur in the purchasing process,but also in the consumption process.
Keywords: C51; D11; D12; 330; consumption function; inventory; utility maximization; promotion anticipation.; Konsumentenverhalten; Nutzentheorie; Theorie